The Early Impact of COVID-19 on Ophthalmology Resident Training and Wellness - Woodfin, Michael; Bojikian, Karine D.; Taravati, Parisa; Ding, Leona; Lee, Michele D.; Feng, Shu (Journal of Academic Ophthalmology, 2020)
Objective The aim of this article is to assess the initial impact of the coronavirus disease 2019 (COVID-19) pandemic on ophthalmology resident training and wellness.Design Online national survey of ophthalmology residents distributed by residency program directors and education coordinators of participating programs.Setting US ophthalmology residency programs during the COVID-19 pandemic (May 20th, 2020 to June 10th, 2020).Participants Ophthalmology residents enrolled in the US residency programs currently in postgraduate years two through four of training.Results Two-hundred thirty-six of 785 (30.1%) residents responded to the survey. One-hundred eighteen of 234 (50.4%) residents reported exposure to known COVID-19 positive patients, and of those exposed, 44 of 118 (37.2%) felt that they did not have adequate personal protective equipment. One-hundred ninety-five of 233 (83.7%) residents reported a decrease in primary surgical cases during the pandemic, with 68 (29.2%) reporting a loss of more than 50 primary cases. One-hundred sixty-four of 234 (70.1%) residents were concerned that the pandemic would negatively impact their surgical skills beyond residency, and 15% reported that they were more likely to pursue fellowship due to the pandemic. 31.0% of residents met criteria of burnout, 9.1% were depressed, and 13.4% had generalized anxiety. Concerns about COVID-19 infection were correlated with increased anxiety and burnout during the pandemic.Conclusions The COVID-19 pandemic has decreased resident surgical and clinical volumes and has negatively impacted ophthalmology residency training. Residents with increased concern for contracting COVID-19 and those actively engaged in a job search had significantly higher odds of increased anxiety.
Keywords: ophthalmology residency; COVID-19; coronavirus; wellness; physician burnout